Randomized controlled trial of 7, 28, vs 42 day stored red blood cell transfusion on oxygen delivery (VO2 max) and exercise duration. Issue 3 (27th December 2020) - Bennett‐Guerrero, Elliott; Rizwan, Sabeen; Rozensky, Russell; Romeiser, Jamie L.; Brittelli, John; Makaryus, Rany; Lin, Jun; Galanakis, Dennis K.; Triulzi, Darrell J.; Moon, Richard E.
Abstract: Background: Few studies have rigorously assessed the impact of red blood cell (RBC) transfusion on oxygen delivery. Several large trials demonstrated no clinical outcome differences between transfusion of shorter‐storage vs prolonged‐storage RBCs. These trials did not directly assess functional measures of oxygen delivery. Therefore, it is not clear if 42‐day stored RBCs deliver oxygen as effectively as 7‐day stored RBCs. Study Design and Methods: Leukocyte‐reduced RBCs were collected by apheresis in AS‐3. Thirty subjects were randomized (1:1:1) to receive 2 units of autologous RBCs at either 7, 28, or 42 days following donation. VO2 max testing, using a standardized protocol to exhaustion, was performed 2 days before (Monday) and 2 days after (Friday) the transfusion visit (Wednesday). The primary endpoint was the percent increase in VO2 max between Monday and Friday. The secondary endpoint was the percent change in duration of exercise for the same time points. Results: Hemoglobin levels decreased by 2.8 ± 1.4 g/dL after donation and increased by 2.1 ± 0.6 g/dL after transfusion. This change in hemoglobin was associated with expected decreases (then increases after transfusion) in VO2 max and exercise duration. No differences were observed between 7‐day and 42‐day RBC transfusion for percent increase in median [IQR] VO2 max (10.5 [0.2‐17.3] vs 10.9 [5.7‐16.8], P = .41) or for percent increase in exercise duration (5.4 [4.1‐6.9] vs 4.9 [2.0‐7.2], P = .91), respectively. Results were similar for 28‐day RBCs and were consistent across the ITT and per‐protocol analysis populations. Conclusion: These data indicate that 42‐day, 28‐day, and 7‐day RBCs have similar ability to deliver oxygen. Abstract : See editorial on page 657–659, in this issue